2017
DOI: 10.1246/bcsj.20170345
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous Crystals of E,E-1,4-Bis(3,5-ditrifluoromethylstyryl)benzene with High Emission Ability

Abstract: E,E-1,4-Bis(2,4-ditrifluoromethylstyryl)benzene (d24CF3) and E,E-1,4-bis(3,5-ditrifluoromethylstyryl)benzene (d35CF3) were synthesized. The d35CF3 crystals grown from solution displayed a unique fibrous form and emitted propagated fluorescence, and a d35CF3 film demonstrated a very low ionization potential of −6.7 eV. Meanwhile, d24CF3 crystals exhibited aggregation-induced emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The development of several π-conjugated oligomers has contributed to the advancement of organic optical and electronic devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, bis-styrylbenzene derivatives (BSDs) and thiophene/phenylene co-oligomers (TPCOs) show remarkable optical and electrical characteristics. Various studies have reported the excellent photophysical properties of BSDs and TPCOs, where 1,4-bis(4trifluoromethylstyryl)benzene and α,ω-bis(biphenylyl) terthiophene (BP3T) show very low amplified spontaneous emission thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…The development of several π-conjugated oligomers has contributed to the advancement of organic optical and electronic devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, bis-styrylbenzene derivatives (BSDs) and thiophene/phenylene co-oligomers (TPCOs) show remarkable optical and electrical characteristics. Various studies have reported the excellent photophysical properties of BSDs and TPCOs, where 1,4-bis(4trifluoromethylstyryl)benzene and α,ω-bis(biphenylyl) terthiophene (BP3T) show very low amplified spontaneous emission thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…Promising materials for the current injection type lasers are mainly π-conjugated oligomers such as thiophene/phenylene co-oligomers (TPCOs) [1][2][3][4][5] and bis-styrylbenzene derivatives (BSDs). [6][7][8][9][10][11] TPCOs had good crystallinity, and when field effect transistors were fabricated using their crystals, they showed a field effect mobility of 0.16 cm 2 V −1 s −1 . 12) Furthermore, it has been reported that 2,5-bis(4-biphenylyl)thiophene (BP1T) was formed into crystals of sub-centimeter size by a vapor-phase growth method, and BPIT crystal was excited with a nitrogen (N 2 ) laser to show an ASE threshold of 27 μJcm −2 .…”
mentioning
confidence: 99%